Use of a local anesthetic and opioid combination in spinal anesthesia in short urologic surgeries - özdemir, Abdullah; Çolak, Mehmet Salih (International Journal of Research in Medical Sciences, 2019)
Background: To investigate how low-dose levobupivacaine affects both surgical comfort and hemodynamics in patients undergoing short urologic procedures using spinal anesthesia. Methods: Our study was conducted prospectively and double-blind. The study group comprised 40 patients aged 18-65 years from the ASA I-III risk group who had undergone short urological interventions, randomly split into two groups. Informed consent and ethics committee approval were received. Using a media approach and placed in the lateral decubitus position, the patients were given spinal anesthesia using 22 G catheter. Group L was given 1.5ml of levobupivacaine (7.5mg) at 0.5% concentration +0.5ml of saline. Group LF was given 1.2ml levobupivacaine (6mg) at 0.5% concentration +25μg fentanyl (0.5ml) +0.3ml saline. Patient data including peripheral oxygen saturation; systolic, diastolic, mean arterial pressure; time to first postoperative need for analgesics, and spinal block characteristics were recorded at 3, 5, 10, 15, 30, 60, 120 and 360minutes after spinal anesthesia. Results: No significant differences were observed in the demographic and hemodynamic data between groups. Motor blocks were seen to wear off more in Group LF than in Group L at 120minutes. Group LF required first postoperative analgesics later than Group L; this difference was not significant. Conclusions: Sufficient anesthesia was achieved in both groups via spinal block using local anesthetic or local anesthetic plus opioid for relatively short urological procedures. The latter group recovered faster.